2019
DOI: 10.1177/1369433219829808
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on screw connections in cold-formed steel walls with cement sheathing

Abstract: This article presents an experimental study on the screw connections between cold-formed steel walls and cement-based boards such as fibercement boards and ferrocement boards. The effect of loading direction, type of sheathing, board thickness, and screw number and spacing were investigated. Tests were performed under shear which is perpendicular to the free edge and also under shear which is parallel to the free edge of the board to simulate the actual behavior of sheathed shear walls. In each case, the peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…According to EN 1994-1-1 [37], push-out tests are the standard means for determining the shear behaviour and capacity of connectors in composite construction -see Figure 25 (b). Therefore, several researchers have adopted this approach to determine the shear behaviour of fasteners connecting coldformed steel sections and various types of boards, including plasterboards [38], timber based boards [5,39] and cement based boards [23]. The latter approach is considered to be more representative of how a typical stud column is loaded in practice, and is therefore employed herein.…”
Section: Shear Behaviour Of Screws Connecting Sheathing To Cold-forme...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to EN 1994-1-1 [37], push-out tests are the standard means for determining the shear behaviour and capacity of connectors in composite construction -see Figure 25 (b). Therefore, several researchers have adopted this approach to determine the shear behaviour of fasteners connecting coldformed steel sections and various types of boards, including plasterboards [38], timber based boards [5,39] and cement based boards [23]. The latter approach is considered to be more representative of how a typical stud column is loaded in practice, and is therefore employed herein.…”
Section: Shear Behaviour Of Screws Connecting Sheathing To Cold-forme...mentioning
confidence: 99%
“…Individual shear connection tests, featuring OSB and plasterboard as the sheathing and a range of steel thicknesses and screw connector sizes, were reported in [14,[17][18][19][20][21][22]. Experimental studies into the shear response of sheathing-to-cold-formed steel connections have also been conducted for various other types of board material, including cement based boards [18,23], calcium silicate boards [22,24], fibre cement boards [25] and Bolivian manganese boards [22].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to improved elastic stiffness and peak load for the ultimate shear capacity of the screw fastener set up. Load directions have been tested by Iuorio (2007) [2] and Abu-Hamd (2019) [7] where both perpendicular and parallel loads are applied to the CFS fasteners to compare the shear capacity, the conclusion of which is that the governing load direction is parallel to the free end; the parallel loading capacity is about 45% higher than that for perpendicular loading. These results are consistent with the thickness of the sheathing findings by (Karabulut and Soyoz, (2017) [8]) whereby the thicker the sheathing board, the higher the ultimate shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the thickness of the sheathing findings by (Karabulut and Soyoz, (2017) [8]) whereby the thicker the sheathing board, the higher the ultimate shear strength. The loading direction also leads to conflicting failure mechanisms, whereby both the parallel and perpendicular loading is governed by screw tilting, but screws loaded in the parallel direction are observed to pull through after tilting (Abu-Hamd (2019) [7]). Li et al, (2020) [6] also noticed difference in the directional orientation of the bamboo itself, for example axial loading of unidirectional flat pressing bamboo panels leads to increased peak loads and elastic stiffness compared to that of double-direction laminated bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…Through experimental research, it is found that the damage threshold load level is highly dependent upon the exterior sheathing. Therefore, extensive research studies on the influence of the sheathing material were performed (Abu-Hamd, 2019; Balh et al, 2014; Fülöp and Dubina, 2004; Mohebbi et al, 2015). The research studies found that double-layer sheathing can significantly improve the energy dissipation, shear strength and elastic stiffness compared to single-layer sheathing.…”
Section: Introductionmentioning
confidence: 99%